Wildlife Trafficking - Wyatt, T. author. aut Link
XI, 215 p.
Keywords: This book provides a unique, comprehensive exploration of the scale, scope, threats and drivers of wildlife trafficking. It also undertakes a distinctive exploration of who the victims and offenders of wildlife trafficking are as well as analysing the stakeholders who are involved in collaborative efforts to end this devastating green crime.